Current correlation functions from a bosonized theory in 3/2+1 dimensions - Fosco, Cesar Daniel (2020)
Within the context of a bosonized theory, we evaluate the current-current correlation functions corresponding to a massive Dirac field in 2+1 dimensions, which is constrained to a spatial half-plane. The boundary conditions are imposed on the dual theory, and have the form of of perfect-conductor conditions. We also consider, for the sake of comparison, the purely fermionic version of the model and its boundary conditions, in the large-mass limit. We apply the result about the dual theory to the evaluation of induced vacuum currents in the presence of an external field, in a spatial half-plane.